Accelerated extracellular matrix turnover during exacerbations of COPD. Issue 1 (December 2015) - Sand, Jannie; Knox, Alan; Lange, Peter; Sun, Shu; Kristensen, Jacob; Leeming, Diana; Karsdal, Morten; Bolton, Charlotte; Johnson, Simon
Abstract Background Exacerbations of chronic obstructive pulmonary disease (COPD) contribute significantly to disease progression. However, the effect on tissue structure and turnover is not well described. There is an urgent clinical need for biomarkers of disease activity associated with disease progression. Extracellular matrix (ECM) turnover reflects activity in tissues and consequently assessment of ECM turnover may serve as biomarkers of disease activity. We hypothesized that the turnover of lung ECM proteins were altered during exacerbations of COPD. Methods 69 patients with COPD hospitalised for an exacerbation were recruited at admission and returned for a 4 weeks follow-up. Competitive ELISAs measuring circulating protein fragments in serum or plasma assessed the formation and degradation of collagen types III (Pro-C3 and C3M, respectively), IV (P4NP 7S and C4M, respectively), and VI (Pro-C6 and C6M, respectively), and degradation of elastin (ELM7 and EL-NE) and versican (VCANM). Results Circulating levels of C3M, C4M, C6M, ELM7, and EL-NE were elevated during an exacerbation of COPD as compared to follow-up (allP <0.0001), while VCANM levels were decreased (P <0.0001). Pro-C6 levels were decreased and P4NP 7S levels were elevated during exacerbation (P <0.0001). Pro-C3 levels were unchanged. At time of exacerbation, degradation/formation ratios were increased for collagen types III and VI and decreased for collagen type IV. Conclusions Exacerbations of COPD resulted in elevated levels of circulating fragments of structural proteins, which may serve as markers of disease activity. This suggests that patients with COPD have accelerated ECM turnover during exacerbations which may be related to disease progression.